2021
DOI: 10.2147/hiv.s341012
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of COVID-19 on Routine HIV Care Services from Health Facilities in Northwest Ethiopia

Abstract: Background There is mounting evidence that the risk of death from COVID-19 among people with HIV could be as much as twice that of the general population. Recent evidence revealed that HIV services has been decreased by 75% and the problem is much more extensive in Ethiopia since most of the logistics for HIV services and fund donated by the good will of NGOs. Understanding the impact of COVID-19 on HIV services is a crucial first step to draw appropriate intervention. Thus, this study aimed to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
2
22
0
1
Order By: Relevance
“…Similarly, another included study in this review conducted among healthcare providers reported ART application service suspension or postponement due to COVID-19 restrictions or short supplies [ 32 ]. A similar study carried out in Northwest Ethiopia reported a substantial decline in ART services between 2019 and 2020 due to a full national lockdown [ 35 ]. Another similar study in China reported difficulties with refilling ART stocks due to lockdowns [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, another included study in this review conducted among healthcare providers reported ART application service suspension or postponement due to COVID-19 restrictions or short supplies [ 32 ]. A similar study carried out in Northwest Ethiopia reported a substantial decline in ART services between 2019 and 2020 due to a full national lockdown [ 35 ]. Another similar study in China reported difficulties with refilling ART stocks due to lockdowns [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Chronic diseases generally account for about 60% of all deaths worldwide. HIV is one of the leading causes of death worldwide, with about 690,000 people dying each year [ 11 , 12 ]. Global efforts to combat HIV have been hampered since the outbreak of the coronavirus (COVID-19), and global funding to respond to the disease has dwindled [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…While clinics in high-prevalence settings were less http://onlinelibrary.wiley.com/doi/10.1002/jia2.26036/full | https://doi.org/10.1002/jia2.26036 likely to report suspending HIV services and appointments, other care-seeking barriers (e.g. lockdown restrictions, transportation and financial barriers, and concerns about COVID-19 exposure) may have presented insurmountable obstacles for patients in these settings, and early data from diverse settings have highlighted sharp decreases in healthcare-seeking for HIV-related services early in the pandemic, including HIV prevention [49,53], diagnosis [24,41,42,[44][45][46][47][48][53][54][55] and treatment [24,43,44,53,55,56], as well as diagnostics and treatment for other infectious diseases and chronic conditions [55][56][57][58]. While some studies in sub-Saharan Africa have reported rebounds in HIV testing and ART initiation [24,59], our findings related to stockouts of second-and third-line ART regimens in high-prevalence and low/lower-income settings are concerning, as the lack of such essential medicines may result in setbacks for both HIV treatment and prevention.…”
Section: Discussionmentioning
confidence: 99%
“…There have been some reports of late presenters of an AIDS-defining lifethreatening condition as a result of difficulties accessing hospital care [32]. In addition, during the COVID-19 pandemic, there have been many reports indicating a reduction in HIV testing rates in many countries [33][34][35].…”
Section: Discussionmentioning
confidence: 99%